The Effect of Hypnotherapy on Stress Level of 1st Year Students of Ners Study Program of Santa Elisabeth College of Health Sciences Medan Year 2024 - Imelda Girsang; Ance Siallagan; Icha Dearmayani Munthe (LPPM Universitas Harapan Bangsa, 2025)
Stress is a condition that occurs as a result of changes in the surrounding environment that are challenging, disrupting the balance of a person's behavior and can lead to a strong response to stress or stress resllting in excessive emotions that interfere with daily activities. This can happen to everyone, including students, therefore treatment is needed, such as hypnotherapy, which is a therapy to overcome a person's cognitions, affection and behavior problems in recurring stress levels. His research aims to analyze whether there is an effect of hypnotherapy on the stress of 1st year students of Stikes Santa Elisabeth Medan 2024. This research uses a one group-posttest design. The sampling technique was random sampling with a sample size of 20 people. The research results showed that 20 respondets had student stress levels before the intervention of 1.90 with a standard deviation of .910. The average reduction in student stress levels after the hypnotherapy intervention was .50 with a standard deviation of .607. paired-test statistical test, obtained a P-value of 0.000, which means there is a mean difference in decreasing student stress levels in a positive direction between before and after being given hypnotherapy an increasing range of influence of hypnotherapy treatment on student stress levels. It is hoped that it can provide input to educational institutions and dormitories in dealing with student stress levels with hypnotherapy.